2018
DOI: 10.5826/dpc.0804a06
|View full text |Cite
|
Sign up to set email alerts
|

Onychoscopy: an observational study in 237 patients from the Kashmir Valley of North India

Abstract: Background: Nail disorders comprise approximately10% of all dermatological conditions. Because diagnosis is not always possible by clinical means alone, additional diagnostic procedures may be required at times. Dermoscopy of nails (onychoscopy) has shown promising results in diagnosing various nail disorders and also avoids time-consuming investigations such as culture and biopsy. Objective: To study the dermoscopic features of various nail disorders to determine the correlation between KOH exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
6
23
1
Order By: Relevance
“…Onychomycosis was the most common nail disorder observed in our study and this was concordant with Puri et al 4 , Bhat YJ et al 5 and Kumar et al 6 with 25%, 34.18% and 34.2% prevalence respectively, while Rathod et al 3 found onychomycosis as the second most common disorder after nail psoriasis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Onychomycosis was the most common nail disorder observed in our study and this was concordant with Puri et al 4 , Bhat YJ et al 5 and Kumar et al 6 with 25%, 34.18% and 34.2% prevalence respectively, while Rathod et al 3 found onychomycosis as the second most common disorder after nail psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was a male preponderance [M:F = 1.46:1] which was similar to the findings of other Indian studies by Puri et al 4 , Rathod et al 3 and Bhat YJ et al 5 This could be because of better accessibility of males to health care facilities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations